SELF TISSUE EXPANDERS IN FACIAL SCAR CORRECTION. - LOGANATHAN SELVARAJ (International Journal of Pharma and Bio Sciences, 2014)
Major challenge in facial scar correction is deficiency of tissue for correction and replacing the tissue with similar colour and texture these challenges are overcome by using tissue expanders. They become more practical and easy way of facial reconstruction surgeries. In our case we used newer version of tissue expanders – Osmotic tissue expanders for correction of depressed scar in forehead region. Osmotic tissue expanders are made of Vinyl pyrrolidone and Methylmetacrylate with in porous silicone shell. Osmotic tissue expanders imbibe the body fluids and expand to the predetermined size. Advantage of using osmotic tissue expanders compared to conventional expanders are avoidance of multiple appointment, decreases the risk of infection and expander punctures. On the negative side osmotic tissue expanders have an uncontrolled rate and direction of expansion which lead to necrosis of tissues and displacement of the device. Many studies state of high rates of complication in tissue expanders like ischemia and necrosis of the tissues, displacement of the device and infection. So careful case selection and judicial use of tissue expanders is needed.